Pentingnya Trasparansi Keuangan Negara Dalam Meningkatkan Integritas dan Meminimalisir Tindak Pidana Korusi di Suatu Negara - Nisak, Khairun; Riza, Safrur; Amiruddin (Ameena Journal, 2023)
Corruption is a serious problem that hinders development and threatens the stability of a country. Efforts to eradicate corruption require effective steps, one of which is increasing the transparency of state finances. Financial transparency involves providing open, clear and easily accessible information about a country's income, expenditure and assets to the public. This article aims to explain the importance of state financial transparency in increasing integrity and minimizing corruption in a country. By conducting a literature review and qualitative review using library research as a way to collect data, this article describes the positive impact of financial transparency in fighting corruption in a country. The results of this study indicate that countries that implement a high level of financial transparency tend to have lower levels of corruption. Financial transparency provides tools for civil society, media and oversight institutions to monitor state financial management and detect potential acts of corruption. In addition, transparency also increases the accountability and integrity of public institutions, and builds public trust in the government. Several countries still face challenges in developing effective financial reporting systems, collecting accurate data, and providing training to relevant government staff. In addition, resistance from parties involved in corrupt practices can also be a barrier. This journal concludes that state financial transparency has an important role in increasing integrity and minimizing corruption in a country. To achieve this, collaborative efforts are needed between the government, supervisory agencies, civil society, and the private sector in strengthening the financial transparency system. Increasing public awareness about the importance of transparency and active participation of the public in overseeing the use of the state budget is also an important factor.